Google Classroom dan Zoommeeting: Alternatif Platform Terhadap Peningkatan Kemampuan Menulis Bahasa Jepang Pelajar Kelas XI IPA 1 SMAN 1 Rengat TP 2020/2021 - Wahyuni, Maya Indah (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
This study aims to determine the influence in Japanese writing skills of students in class XI IPA 1 at SMAN 1 Rengat during distance learning activities used googleclassroom and zoommeeting. This research is a classroom action research conducted in two cycles, each cycle consisting of three meetings with a duration of 60 minutes for each meeting and 34 person students. Based on the results of the research, students who completed the first cycle used googleclassroom were 6 students, meanwhile the highest score was 81.29 only one student while the lowest score was 24, 84. Then the second cycle was used googleclassroom and zoommeeting about 22 students completed, white the highest score was 90.32 got one student, and the lowest score was 40.55. Afterwards 14 students didn`t complete. Through a questionnaire given, students answered that distance learning was not as effective as face-to-face learning because when the teacher explained that the internet signal suddenly disappeared, the increase in Japanese language skills was not optimal, materials were not understood due to limited study time. But the use of zoommeeting can help deliver material better than the use of google classroom. So, the use of the googleclassroom platform and zoommeeting during distance learning can help improve students' Japanese writing skills.